Stable isotope analyses of ancient and modern Adélie Penguin (Pygoscelis adeliae) mummies from the Ross Sea Region, Antarctica - Kristan, Allyson K.; Emslie, Steven D.; Patterson, William P. (Polar Biology, 2019)
We performed stable carbon (δ13C) and nitrogen (δ15N) isotope analyses of 12 ancient Adélie penguin (Pygoscelis adeliae) chick mummies recovered from abandoned colonies in the Ross Sea region, Antarctica, to investigate isotopic variation and fractionation over time. We also examined latitudinal variation in penguin diet to address if the modern dietary pattern (an increase in krill as dominant prey to the north) in this region has existed in the past or if this is a recent phenomenon. The ancient mummies range in age from > 48,000 14C years before present (BP) to ~ 500 calendar years BP. Feather, skin, bone, and toenail samples were analyzed from each individual where available. Identical analyses were performed on five modern mummified Adélie penguin chick carcasses and breast feathers of ten recently dead chicks from each of two active colonies, Cape Hallett and Adélie Cove. We found significantly lower δ15N values in Cape Hallett modern chicks as compared to those from Adélie Cove, indicating an entire trophic-level difference in modern diet that agrees with other studies in this region. The ancient mummies exhibited consistent isotopic fractionation of δ13C among the four different tissues through time. Variation in δ15N and δ13C values was greater in bone and skin than in feather or toenail, but δ15N in all four tissues indicated similar dietary trends with latitude as occurs in this region today. These results provide insight into the dietary variability of Adélie penguins across the Ross Sea region and a framework for similar analyses with other avian species.